Human primary skeletal muscle‐derived myoblasts and fibroblasts reveal different senescent phenotypes - Thomas G. Francis; Oihane Jaka; Georgina M. Ellison‐Hughes; Norman R. Lazarus; Stephen D.R. Harridge (Wiley, 2022)
Abstract Background The age‐related loss of muscle mass and quality, sarcopenia, has many contributing factors, one of which may be cellular senescence, but this is not well defined in human skeletal muscle. Method Primary cells were isolated from biopsy samples of the vastus lateralis muscle from healthy adult males (n = 6, 22 ± 1 years), sorted (magnetic activated cell sorting) and chemically induced (doxorubicin, DOX, 0.2 μM) to a senescent state. This allowed the parallel and simultaneous investigation of the two main skeletal muscle‐derived cell types: satellite cell‐derived CD56+ve/desmin+ve myoblasts (muscle precursor cells) and CD56− ve/TE7+ve fibroblasts (at >95% purity). Both cell types were followed for up to 35 days post DOX treatment with a combination of quantitative immunocytochemistry and qRT‐PCR for senescent markers and senescence‐associated secretory phenotype (SASP) factors. Results Myoblasts and fibroblasts showed temporal and quantitative differences in many of the senescence markers studied. p16 protein expression increased across the time course (P < 0.0001) with no difference between cell types, whereas at the mRNA level, myoblasts showed increased p16 expression from 4 days post treatment (FC = 3.03 ± 0.99), and in fibroblasts, this appeared later at 10 and 35 days post DOX treatment (FC = 8.09 ± 2.46, P < 0.0001). Both myoblasts (FC = 8.83 ± 1.72) and fibroblasts (FC = 2.33 ± 1.10) showed significant increases in p21 mRNA (P < 0.0001), which remained elevated in the myoblast cell populations across the 35‐day time course but returned to baseline in the fibroblasts from 4 days post DOX treatment. Within 35 days post DOX treatment, all cell populations of both myoblasts and fibroblasts had reached 100% SA‐β‐Gal‐positive cells (P < 0.05). γH2aX expression (a marker of DNA damage) increased 1 day after DOX treatment in the myoblasts (FC = 3.3 ± 1.1, P < 0.05) but returned to baseline within 4 days post DOX treatment, whereas fibroblasts showed a similar trend that did not reach statistical significance. Significant reductions in expression of the proliferation marker Ki67 1 day post DOX treatment were seen in both cell types and were maintained throughout the time course (FC = 0.11 ± 0.07, P < 0.0001). Significant changes over the time course were also observed in mRNA expression of selected SASP factors (e.g. PAI‐1, MMP3, and IGFBP3, P < 0.05). Conclusions Neither cellular senescence nor sarcopenia is fully understood. The present data on human primary myoblasts and fibroblasts obtained from the same tissue sample show that senescence is a complex, non‐linear, and dynamic cellular process which shows intra‐ and inter‐cell variability.